Risk Management of Training Services in PT MMK - Bovi Mutiara Sofi; Heti Mulyati; Deni Achmad Soeboer (Bina Nusantara University, 2021)
One of the business training services that is rapidly grown is at the Occupational Health and Safety (Keselamatan dan Kesehatan Kerja (K3)) training services. PT MMK is a K3 training service company that has been developed since 2016. However, PT MMK faces some risks in its business activities. There are various problems and potential risks faced by PT MMK, so it needs a business risk management observation. The research aimed to identify and analyze the level of risk faced by PT MMK by applying a quantitative method. The primary and secondary data were used. Sampling was carried out by using non-probability techniques with purposive sampling through the expert judgment approach. There were eight respondents in the research. Meanwhile, the applied analytical methods were Cochran analysis and Godfrey risk map. The result shows that based on four divisions, PT MMK has 30 internal risks and 8 external risks. There are 4 low-level risks, 14 moderate-level risks, 19 high-level risks, and 1 extreme-level risk. Based on the highest risks, PT MMK should do detailed budgeting, so there is no over cost based on the previous training budget. Moreover, the company can also expand its market share to the other companies by offering its training.